Propane (HC – 290) as an Alternative Refrigerant in the Food Transport Refrigeration Sector in Southern Africa – a Review - Thomas Kivevele (Automotive Laboratory of Universitas Muhammadiyah Magelang in collaboration with Association of Indonesian Vocational Educators (AIVE), 2022)
Most of the food transport trucks in Sothern Africa are equipped with refrigeration and air conditioning systems filled with fluorocarbon refrigerants such as R404A to facilitate the heat transfer process. These refrigerants are synthetic chemicals and have high potential to cause global warming and damage to the ozone layer. Currently, natural refrigerants are considered as alternatives to these man-made refrigerants to mitigate some of the environmental risks. The natural refrigerants are the substances that occur in nature such as hydrocarbons (HC), ammonia, and carbon dioxide. These type of refrigerants have been in the market for many years, but in some applications such as domestic refrigerators, heat pumps, chillers, and air conditioners, whereas fluorocarbons are the mostly used in the food transport refrigeration systems. Natural refrigerants such as propane (HC – 290) are now penetrating the market in food transport refrigeration systems where previously fluorocarbons were the favoured option. Therefore, this work reports the possibilities of using non-fluorinated hydrocarbon/natural refrigerant (propane – R290) in the food transport refrigerated systems in Southern Africa; a case study of South Africa. R290 has the potential to lower greenhouse gases emissions compared to hydrofluorocarbons (HFCs) which are widely used in most of the existing food transport refrigeration systems in South Africa. R290 has negligible Global Warming Potential (GWP) of 3 which is well below the global threshold value of 150. The review revealed that refrigeration capacity of R290 is in the average of 10 – 30% higher than commonly used fluorocarbon refrigerants such as R404A and R134A. Since R290 is labeled as a flammable refrigerant, the present study also reviews its flammability safety measures.